Coordinated Portfolio Investment Survey Guide. (International Monetary Fund, 1996)
The coordinated Portfolio Investment Survey Guide is provided to assist balance of payments compilers in the conduct of an internationally coordinated survey of security holdings being conducted under the auspices of the IMF with reference to year-end 1997. The Guide has two main purposes: to set out the objectives of the Coordinated Survey; and to provide practical advice on how to prepare, organize, and conduct a national survey. The appendices include three model survey forms, a glossary of security terms, a listing of the major security databases that national compilers may find useful in their work, and a method for reconciling security position and transactions data.